2012
DOI: 10.1016/j.socscimed.2012.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood-level stressors, social support, and diurnal patterns of cortisol: The Chicago Community Adult Health Study

Abstract: Neighborhood disadvantage has consistently been linked to increased rates of morbidity and mortality, but the mechanisms through which neighborhood environments may get “under the skin” remain largely unknown. Differential exposure to chronic environmental stressors has been identified as a potential pathway linking neighborhood disadvantage and poor health, particularly through the dysregulation of stress-related biological pathways such as cortisol secretion, but the majority of existing observational studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 51 publications
8
93
0
Order By: Relevance
“…The altered decline in diurnal cortisol might also be a consequence of stress or disrupted rest/activity cycles induced by fatigue, since in other studies higher evening cortisol levels had been associated with work-related stress [40][41][42], sleep disturbances [43], disrupted rest/activity cycles [44], or lack of social support [42,45].…”
Section: Discussionmentioning
confidence: 97%
“…The altered decline in diurnal cortisol might also be a consequence of stress or disrupted rest/activity cycles induced by fatigue, since in other studies higher evening cortisol levels had been associated with work-related stress [40][41][42], sleep disturbances [43], disrupted rest/activity cycles [44], or lack of social support [42,45].…”
Section: Discussionmentioning
confidence: 97%
“…Experimental studies report that behavioral and endocrine changes occur after an acute psychological stress test, including cigarette craving (Buchmann et al, 2010), decreased physical activity (Hamer, 2012;Rutters et al, 2009), increased alcohol intake (Pohorecky, 2010), HPA axis activation (Born et al, 2010;Strahler et al, 2010) and inflammatory responses (Carpenter et al, 2010). Furthermore, population-based and patient studies have shown associations between psychosocial stress, chronic HPA axis activation (Karb et al, 2012), disruption of the circadian rhythm (Dedert et al, 2012), sleep deprivation (Mezick et al, 2009), depression (Musselman et al, 1998), type 2 diabetes (Puustinen et al, 2011) and cardiovascular disease (Neylon et al, 2013). Up until now, none of the previous studies on stressful life events have studied mediating factors, therefore, the second aim of our study is to evaluate whether the suspected relationship between the number of stressful life events and mortality is mediated by behavioral factors and morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that individuals living in neighborhoods with increased levels of perceived stressors had an increase of cortisol throughout the day and evening, starting three hours after waking, and lower overall cortisol mean (Karb et al, 2012).…”
Section: Associations Between Psychosocial Stress and Physiological Dmentioning
confidence: 94%
“…It is possible that neighborhood stress can influence disease through neuroendocrine pathways (Steptoe & Feldman, 2001). Flattened salivary cortisol rhythms have been observed in individuals who live in neighborhoods with high levels of both perceived (e.g., perceived violence) and observed (e.g., homicide rates) stressors (Karb, Elliott, Dowd, & Morenoff, 2012). Flattened diurnal slopes and flatter decline from 30 minutes post-awakening to about two hours post-awakening were associated with neighborhood poverty (Hajat et al, 2015).…”
Section: Neighborhood Stress and Physiological Disruption (Figure 1 Amentioning
confidence: 99%
See 1 more Smart Citation